2015
DOI: 10.4103/2008-322x.176909
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of amblyopia and refractive errors among primary school children

Abstract: Purpose:To determine the prevalence of amblyopia and refractive errors among 7 to 12-year-old primary school children in Tehran, Iran.Methods:This population-based cross-sectional study included 2,410 randomly selected students. Visual acuity was tested using an E-chart on Yang vision tester. Refractive errors were measured by photorefractometry and cycloautorefraction. Strabismus was checked using cover test. Direct ophthalmoscopy was used to assess the anterior segment, lens opacities, red reflex and fundus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 28 publications
5
58
3
1
Order By: Relevance
“…During further analysis, the spherical values agreed well with the emmetropia group ( P  = 0.33) compared with the hyperopia group ( P  < 0.0001). Regarding the cylindrical results, several researchers agreed with the consistency of the cylindrical power between the device and CR 13, 15 , whereas others did not 16, 17 . In the present study, the plusoptiX overestimated the the cylindrical power in all groups, thus resulting in the partial or total underestimation of SE (all P  < 0.0001).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…During further analysis, the spherical values agreed well with the emmetropia group ( P  = 0.33) compared with the hyperopia group ( P  < 0.0001). Regarding the cylindrical results, several researchers agreed with the consistency of the cylindrical power between the device and CR 13, 15 , whereas others did not 16, 17 . In the present study, the plusoptiX overestimated the the cylindrical power in all groups, thus resulting in the partial or total underestimation of SE (all P  < 0.0001).…”
Section: Discussionmentioning
confidence: 81%
“…The plusoptiX has been reported by the majority of studies to underestimate children’s refractive error and to have higher accuracy in myopic children than hyperopic children 13–15 . In the present study, the plusoptiX A12C led to a considerable shift towards myopic values (0.45 D), particularly in the hyperopia group (1.62 D), because of normal accommodation.…”
Section: Discussionmentioning
confidence: 99%
“…Amblyopia is a unilateral or infrequently bilateral decreased best corrected visual acuity (BCVA) with no organic ocular lesion 1, 2, 3, 4, 5. According to the literature, amblyopia prevalence ranges from 0.70% to 5% in different reports 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, amblyopia prevalence ranges from 0.70% to 5% in different reports 6, 7, 8, 9. Authors have found an amblyopia prevalence of 2.30% in primary school children of Tehran, Iran (2013) with a diagnostic criterion of BCVA ≤ 20/40 1 . Anisometropia and strabismus are the most common causes of amblyopia, and in some cases, both of them might be observed simultaneously 1 …”
Section: Introductionmentioning
confidence: 99%
“…Since iris color is a known risk factor for certain eye-related diseases, examining the relationship of iris color with unstudied eye diseases may yield valuable results. Given the high prevalence of refractive errors, amblyopia, and strabismus in Iranian children (15)(16)(17), as well as the lack of study on the relationship of iris color with amblyopia and strabismus, a study in this regard seemed necessary.…”
Section: Introductionmentioning
confidence: 99%